Therapeutic administration of IL-15 superagonist complex ALT-803 leads to long-term survival and durable antitumor immune response in a murine glioblastoma model - Mathios, Dimitrios (Int J Cancer, 2015)
Glioblastoma is the most aggressive primary central nervous system malignancy with a poor prognosis in patients. Despite the need for better treatments against glioblastoma, very little progress has been made in discovering new therapies that exhibit superior survival benefit than the standard of care. Immunotherapy has been shown to be a promising treatment modality that could help improve clinical outcomes of glioblastoma patients by assisting the immune system to overcome the immunosuppressive tumor environment. Interleukin-15 (IL-15), a cytokine shown to activate several effector components of the immune system, may serve as an excellent immunotherapeutic candidate for the treatment of glioblastoma. Thus, we evaluated the efficacy of an IL-15 superagonist complex (IL-15N72D:IL-15RαSu-Fc; also known as ALT-803) in a murine GL261-luc glioblastoma model. We show that ALT-803, as a single treatment as well as in combination with anti-PD-1 antibody or stereo-tactic radiosurgery, exhibits a robust antitumor immune response resulting in a prolonged survival including complete remission in tumor bearing mice. In addition, ALT-803 treatment results in long-term immune memory against glioblastoma tumor rechallenge. Flow cytometric analysis of tumor infiltrating immune cells shows that ALT-803 leads to increased percentage of CD8+-cell infiltration, but not the NK cells, and IFN-γ production into the tumor microenvironment. Cell depletion studies, in accordance with the flow cytometric results, show that the ALT-803 therapeutic effect is dependent on CD4+ and CD8+ cells. These results provide a rationale for evaluating the therapeutic activity of ALT-803 against glioblastoma in the clinical setting.